Masalah Sosial dalam Novel Laut Bercerita Karya Leila S. Chudori dan Implikasinya dalam Pembelajaran Teks Novel - Yolanda, Armila; Asri, Yasnur (Journal of Education Language and Innovation, 2023)
This research aims to describe social problems and causes of social problems contained in the novel Laut Cerita by Leila S. Chudori. This type of research is qualitative research that is content analysis using descriptive methods. This research data is in the form of words, phrases, sentences, and discourses that indicate social problems in the novel Laut Cerita by Leila S. Chudori. This research data collection technique is to read and understand the novel to gain a clear understanding of this novel, classify data, and infer data related to social problems. Based on the results of the study, it can be concluded several things as follows. First, the social problems that occur in the novel are the problems of poverty, population, crime, and biocracy. Second, the causes of social problems in the novel Laut Cerita, namely economic factors and cultural factors. Social problems in the novel can be used as learning material for literary appreciation for XII grade high school, namely in learning Basic Competencies to show honest, caring, polite behavior, and responsibility in the use of Indonesian to understand and present novels. Based on the results of the study, it can be concluded that social problems in the novel Laut Cerita arise due to exposure to the speech of characters and narrators and the actions of figures that reflect social problems.